STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER SISWA - Muhammad Haris Afifudin; Novita Vera Anggraini; Yasinta Ningrun; Zidni ‘Ilma Nafi’a (Al Madjid : jurnal Pendidikan Islam, 2025)
Many symptoms appear as signs of moral decline such as free association, violence, crime, and other deviant and reprehensible behavior. Some of the impacts that have been seen include the lack of children's ability to communicate, wanting everything instant without having to know the process, having an egotistical character and many more. This then needs to be realized that it is the responsibility of parents, educators, society, even the nation and state to protect children, especially in the field of morals and character. Here, teachers have a major role in shaping students' character through role models, cooperation between teachers, and positive behavioral habits. In shaping the character of students who are moral, this study identifies effective curriculum management strategies, such as the development of relevant syllabuses, the use of interactive teaching methods, and ongoing teacher training. In addition, this journal emphasizes the importance of collaboration between stakeholders, including teachers, supervisors, parents, and communities, as well as the use of information technology to improve the quality of Islamic religious education. And the implementation of effective strategies for Islamic Education teachers instills leadership character, honesty, and noble morals in students. So it can be concluded that the environment and rapid technological developments have a high influence on students' character, thus causing a decline in students' character, especially in terms of morals and ethics.